New Trends in Environmental Engineering, Agriculture, Food Production, and Analysis - Janczukowicz, Wojciech; Rodziewicz, Joanna; Iwaniak, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue presents the latest advances in agriculture, aquaculture, food technology and environmental protection and engineering, discussing, among others, the following issues: new technologies in water, stormwater and wastewater treatment; water saving, lake restoration; new sludge and waste management systems; biodiesel production from animal fat waste; the microbiological quality of compound fish feeds for aquaculture; the role of technological processes to improve food quality and safety; new trends in the analysis of food and food components including in vitro, in vivo, and in silico analyses; and functional and structural aspects of bioactivities of food molecules.